Role of Epigenetics in the Pathogenesis, Treatment, Prediction, and Cellular Transformation of Asthma. (15th September 2021) - Wasti, Binaya; Liu, Shao-kun; Xiang, Xu-Dong
Abstract : Asthma is a mysterious disease with heterogeneity in etiology, pathogenesis, and clinical phenotypes. Although ongoing studies have provided a better understanding of asthma, its natural history, progression, pathogenesis, diversified phenotypes, and even the exact epigenetic linkage between childhood asthma and adult-onset/old age asthma remain elusive in many aspects. Asthma heritability has been established through genetic studies, but genetics is not the only influencing factor in asthma. The increasing incidence and some unsolved queries suggest that there may be other elements related to asthma heredity. Epigenetic mechanisms link genetic and environmental factors with developmental trajectories in asthma. This review provides an overview of asthma epigenetics and its components, including several epigenetic studies on asthma, and discusses the epigenetic linkage between childhood asthma and adult-onset/old age asthma. Studies involving asthma epigenetics present valuable novel approaches to solve issues related to asthma. Asthma epigenetic research guides us towards gene therapy and personalized T cell therapy, directs the discovery of new therapeutic agents, predicts long-term outcomes in severe cases, and is also involved in the cellular transformation of childhood asthma to adult-onset/old age asthma.